HUBUNGAN ANTARA KEMANDIRIAN BELAJAR, SIKAP SISWA TERHADAP PEMBELAJARAN MATEMATIKA DAN KEMAMPUAN METAKOGNISI DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS X SEMESTER GENAP SMK MUHAMMADIYAH PRAMBANAN KABUPATEN SLEMAN TAHUN AJARAN 2015/2016 - Doni Susanto; Uswatun Khasanah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
During this time some students get assumption that mathematics is a difficult lesson. The low mathematics outcomes learning is considered having a relation with the self regulated learning, the students’ attitude towards the mathematics learning and the students’ metacognition ability. This research is purposed to know is there or not about the positive relation and significance between the self regulated learning, the students’ attitude towards the mathematics learning and the metacognition ability with the mathematics learning outcomes of students of grade X in even semester in Muhammadiyah vocational school of Prambanan in Sleman regency in the academic year of 2015/2016. The population in this research is all of the classes of X TP (TPA, TPB, TPC, TPD) in Muhammadiyah vocational school of Prambanan. The sampling technique used is purposive sampling which is based on the direction from the teacher and class X TPC is taken to be the sampling class. The data collecting technique used is the questioner technique and test which is the determination and the consistence is measured using the validity and reliabiliti test. Pre-test covers normality test, independence test, and linearity test. Meanwhile, data analysis for testing the hypothesis uses the regression and correlation analysis. The research’s result shows that there are the positive relation and significance between the self regulated learning, the students’ attitude towards the mathematics learning and the metacognition ability with the mathematics learning outcomes. Keyword: Self Regulated Learning, Students’ Attitude towards the Mathematics Learning, Metacognition Ability, Mathematics Learning Outcomes